A COMPACT TEA CO2 LASER FOR FIELD-BASED SPECTROCHEMICAL ANALYSIS OF GEOLOGICAL SAMPLES - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1993)
A compact capacitor-transfer TEA CO2 laser of 180 m3 output energy and 50 ns pulse duration in half width was designed and constructed for field use. This laser is suitable for laser microprobe spectrochemical analysis on geological and mining samples. Experiments show that the use of helium as a surrounding gas suppresses the continuous emission spectrum of the plasma, thus increasing the S/N ratio. Using glass as standard samples. the minimum detectable concentrations are estimated with Zn neutral line and F ionic line to be 60 ppm and 500 ppm, respectively.